A Study on Binge Watching and Its Association with Sleep Pattern - A Cross Sectional Study among Medical College Students in Kancheepuram District, Tamil Nadu - Abirami Srinivasan; Shanthi Edward; Anantha Eashwar (National Journal of Community Medicine, 2021)
Background: Binge-watching is a phenomenon of recent interest, as many people all over the world have started watching a lot web-series and movies in Over the Top (OTT) platforms. By definition, binge watching is watching 3 to 6 episodes continuously without any breaks without any feeling of guilt associated with it. Binge-watching can lead to sedentary lifestyle and create problems in personal relationships, causing people to procrastinate important things in their professional/work life, reduced sleep time, insomnia and weight gain.